1993
DOI: 10.1152/ajpheart.1993.264.4.h1154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epoxyeicosatrienoic acids on isolated hearts and ventricular myocytes

Abstract: Effects of cytochrome P-450 metabolites of arachidonic acid, epoxyeicosatrienoic acids (EETS; 5,6-EET, 8,9-EET, 11,12-EET, and 14,15-EET), were examined in isolated guinea pig hearts and ventricular myocytes. Addition of 1-16 ng/ml EETs to normal isolated hearts produced no effects on contractility or coronary pressure. In hearts subjected to 60 min of low-flow ischemia, impairment of contractility and declines in heart rate and coronary perfusion pressure were similar in the presence or absence of 1 ng/ml EET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 0 publications
2
52
0
Order By: Relevance
“…A sulfaphenazole-sensitive CYP2C9-like enzyme has been demonstrated in rat arteries and is implicated in the production of the eicosanoid 11,12-EET (9). Interestingly, 11,12-EET was shown to exacerbate contractile dysfunction after ischemia and reperfusion (28). Another metabolite, 14,15-EET, has been shown to be responsible for the negative inotropic effect of bradykinin (29).…”
Section: Discussionmentioning
confidence: 99%
“…A sulfaphenazole-sensitive CYP2C9-like enzyme has been demonstrated in rat arteries and is implicated in the production of the eicosanoid 11,12-EET (9). Interestingly, 11,12-EET was shown to exacerbate contractile dysfunction after ischemia and reperfusion (28). Another metabolite, 14,15-EET, has been shown to be responsible for the negative inotropic effect of bradykinin (29).…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable controversy regarding the role of cytochrome P450s in the heart, notably the beneficial versus the detrimental effects of arachidonic acid metabolites [31,34,35,39,40,77,78]. We have demonstrated that EETs play a significant role in the improved postischemic functional recovery in isolated mouse hearts overexpressing CYP2J2 [31,34,35,57,78].…”
Section: Cardioprotective Signaling Pathwaysmentioning
confidence: 94%
“…Moffat and colleagues showed that EETs (either 5,6-or 11,12-EET) protected against ischemia-reperfusion injury in isolated hearts and ventricular myocytes (18). Other effects of EETs include direct inhibition of cell death in culture induced by hypoxiareoxygenation, hydrogen peroxide, and serum deprivation.…”
Section: Discussionmentioning
confidence: 99%